Telaah Historis Fenomena Generasi Elegan di Indonesia: Study tentang Kegiatan Keislaman dari Masa Ke Masa - Zaitur Rahem (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2017)
Character number generation in the Czech nation is constantly highlighted many circles. Facts moral degradation is characterized by the proliferation of sexual misconduct that occurred. Both in the corridors of sexual harassment, the behavior of social disharmony, crimininality and procedures of everyday speech. The waning charisma number of figures is also a reflection of the collapse of the building bagia elegance in this auspicious land. public trust in the leadership also declined. Very fast. This reality has become a national concern, because it is considered to create a rift here and there. Crystallization of these concerns is feared will impact even further. Namely, these people will be losing their identity as a civilized nation. The focus of the study in this paper-related symptoms network perilakumanusia in Sumenep amid great fanfare praduk progress of technology and science. Method is a qualitative study, with ethnographic approach. Engineering data tracking by throwing a question and there (snowball sampling). From the study conducted found that the character of some people experience significant changes. The reason, because they trap technology products, relationships, and sociological issues cornucopia is often not filtered out.